Pengaruh Tepung Komposit Jagung (Zea mays l), Kacang Hijau dan Ubi Jalar Kuning terhadap Tingkat Pengembangan dan Daya Terima Bolu Kukus - Yuliyanti, Nela Dwi; , Fitriana Mustikaningrum, S.Gz, M.Sc; , Endang Nur W, S.St., M.Si.Med (2016)
Introduction: Corn, green beans and yellow sweet potatoes can be processed into flour through drying and refining and also can be used as raw materials in substituting wheat flour. The corn flour, green beans flour and yellow sweet potatoes flour substitution in making steamed sponge cake can reduce the societies' dependence of wheat flour, so it can be developed into manufacture of food products as steamed sponge cake. Objective: The purpose of the research is to know the effect of corn composite flour (zea mays l), green beans and yellow sweet potatoes toward development and receptivity of steamed sponge cake. Research Method: Research method of this research is experimental research with full random design using 3 treatments of the composite flour composition Effect, they are 20%: 20%: 600%, 25%: 25%: 50% and 30%: 30%: 40%. Data analysis of steamed sponge cake development and consumer receptivity are analyzed by using statistic test method One Way Anova with 95% significant ratio. Result: ANOVA p value indicates that the steamed sponge cake is 0,110. ANOVA results showed that the p value steamed sponge cake receptivity to 0,947 colors, the scent of 0,573, 0,416 taste, 0,845 texture and overall 0,851. Conclusion: There is no effect of corn composite flour composition, green beans and yellow sweet potatoes in steamed sponge manufacture toward the development level. Color, flavor, texture and overall steamed sponge cake. The most preferred steamed sponge cake by the panelists is steamed sponge cake with composite flour effect 30%:30%:40%. Suggestion: There should be more research on the steamed sponge cake composite flour manufacture in order to get good color, aroma, taste, texture and overall. Keywords: composite flour, corn, green beans, yellow sweet potato, development toward, receptivity level, steamed sponge cake.